MERANCANG RPP INOVATIF DALAM PROGRAM MERDEKA BELAJAR PADA MGMP IPS SMP SE-KABUPATEN JEMBER - Sri Kantun; Dwi Herlindawati; Lisana Oktavisanti M (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
The design of the RPP in the “Merdeka Belajar” program simplifies the making of lesson plans on one sheet. The three core components of the lesson plan are learning objectives, learning activities, and assessments. Therefore, it is necessary to immediately take concrete and innovative steps be able to produce an innovative RPP that can implement the true and complete "Merdeka Belajar" program. The purpose of this activity is to provide an understanding of the design of the lesson plans in the "Merdeka Belajar" program, by chang the technique of preparing the lesson plans which so far have been made in sheets into one sheet. The method in this activity is the lecture method and online demonstration. Community Service Activities with the theme Designing Innovative Lesson Plans in the Independent Learning Program at the Social Studies MGMP of Junior High Schools in Jember Regency had a positive impact. Social Studies teachers have become more aware of the Innovative RPP for independent learning launched by the Minister of Education and Culture